IL-5 mediates monocyte phenotype and pain outcomes in fibromyalgia. Issue 5 (May 2021) - Merriwether, Ericka N.; Agalave, Nilesh M.; Dailey, Dana L.; Rakel, Barbara A.; Kolker, Sandra J.; Lenert, Melissa E.; Spagnola, William H.; Lu, Ying; Geasland, Katharine M.; Allen, Lee-Ann H.; Burton, Michael D.; Sluka, Kathleen A.
Abstract : Abstract: Fibromyalgia (FM) is characterized by widespread chronic pain, fatigue, and somatic symptoms. The influence of phenotypic changes in monocytes on symptoms associated with FM is not fully understood. The primary aim of this study was to take a comprehensive whole-body to molecular approach in characterizing relationships between monocyte phenotype and FM symptoms in relevant clinical populations. Lipopolysaccharide-evoked and spontaneous secretion of IL-5 and other select cytokines from circulating monocytes was higher in women with FM compared to women without pain. In addition, greater secretion of IL-5 was significantly associated with pain and other clinically relevant psychological and somatic symptoms of FM. Furthermore, higher levels of pain and pain-related symptoms were associated with a lower percentage of intermediate monocytes (CD14 ++ /CD16 + ) and a greater percentage of nonclassical monocytes (CD14 + /CD16 ++ ) in women with FM. Based on findings from individuals with FM, we examined the role of IL-5, an atypical cytokine secreted from monocytes, in an animal model of widespread muscle pain. Results from the animal model show that IL-5 produces analgesia and polarizes monocytes toward an anti-inflammatory phenotype (CD206 + ). Taken together, our data suggest that monocyte phenotype and their cytokine profiles are associated with pain-related symptoms in individuals with FM. Furthermore, our data show that IL-5 has a potential role in analgesia in an animal model of FM. Thus, targeting anti-inflammatory cytokines such as IL-5 secreted by circulating leukocytes could serve as a promising intervention to control pain and other somatic symptoms associated with FM. Abstract : Supplemental Digital Content is Available in the Text.Clinical and preclinical data suggest a significant antinociceptive function of IL-5 across the peripheral nervous and immune systems in women with fibromyalgia.